LncRNA nuclear receptor subfamily 2 group F member 1 antisense RNA 1 (NR2F1-AS1) aggravates nucleus pulposus cell apoptosis and extracellular matrix degradation. Issue 2 (1st February 2022) - Du, Longlong; Li, Xuefeng; Gao, Qimeng; Yuan, Puwei; Sun, Yindi; Chen, Yingpu; Huang, Bo; Deng, Yu; Wang, Baohui
ABSTRACT: Emerging reports uncover that long noncoding RNAs (lncRNAs) help regulate intervertebral disc degeneration (IVDD). Here, we probe the function of lncRNA nuclear receptor subfamily 2 group F member 1 antisense RNA 1 (NR2F1-AS1) in IVDD. Quantitative reverse transcription-polymerase chain reaction (qRT-PCR) was applied to verify the expression of NR2F1-AS1 and miR-145-5p in nucleus pulposus (NP) tissues from IVDD patients or NP cells dealt with IL-1β or TNF-α. Flow cytometry or the TdT-mediated dUTP nick end labeling (TUNEL) assay was performed to validate the apoptosis of NP cells with selective regulation of NR2F1-AS1 and miR-145-5p. ECM-related genes, FOXO1, Bax, and Bcl2 were evaluated by qRT-PCR or Western blot (WB). The targeted relationships between NR2F1-AS1 and miR-145-5p, miR-145-5p and FOXO1 were testified by the dual-luciferase reporter assay and the RNA immunoprecipitation (RIP) assay. Our outcomes substantiated that NR2F1-AS1 was up-regulated, while miR-145-5p was down-regulated in intervertebral disc tissues of IVDD patients or NP cells treated with IL-1β or TNF-α. Besides, overexpressing NR2F1-AS1 intensified ECM degradation and NP cell apoptosis induced by IL-1β, while knocking down NR2F1-AS1 or up-regulating miR-145-5p reversed IL-1β-mediated effects in NP cells. Meanwhile, NR2F1-AS1 choked miR-145-5p and abated its effects in NP cells. This study confirms that NR2F1-AS1 modulates IVDD progression by up-regulating the FOXO1 pathway through the sponge of miR-145-5p as a competitive endogenous RNA (ceRNA).